UPLINK CAPACITY MODELING IN 3G CELLULAR SYSTEM - Hiu, Sheau Ying (Universiti Malaysia Sarawak, 2004)
The Wideband Code Division Multiple Access (WCDMA) has been identified as one of the technologies used to meet the high capacity and high bandwidth requirements of the third generation (3G) cellular system. The capacity performance of WCDMA is affected by various factors. Spectrum efficiency, cluster size, reuse distance, and modulation schemes can significantly improve the system capacity. The processes involved in determining 3G cellular systems capacity are very different from those used in 2G or 2.5G cellular systems, due to two main reasons. First is the fact that the cell edge in 3G is continuously moving according to the traffic load, making dimensioning ambiguous. The second challenge is an outcome of the multiple data rates and switching modes that supported by the 3G networks. Hence, traffic and capacity analysis for such mixed services is important to include several capacity modeling such as Pole Capacity Model and Erlang Capacity Model. Since 3G services can be asymmetrical for uplink and downlink, this project only concentrate on development of these models in the uplink direction, which includes the above factors to accurately estimate the system capacity. During analysis, it requires the application of system simulation by using Matlab to obtain capacity figures with some evaluation assumption parameters